Guimarães: Circular Economy Towards a Sustainable City - Jorge Cristino, Isabel Loureiro, Carlos Ribeiro, Dalila Sepúlveda Candida Vilarinho (European Journal of Sustainable Development, 2017)
Guimarães, is a medium size city located in the North of Portugal. Since 2015 a program was launched challenging the city to stablish a roadmap for the sustainable development of the Territory. One of the goals was to develop a concept for Circular Economy based in our own city context and vision. A set of projects were stablished from waste valorization. Also to projects focused on promoting social affairs issues were developed having impact on citizens’ quality of life. This paper aims to present the concept under the framework of Guimarães Circular Economy program presenting social, economic and environmental impacts. Keywords: Circular Economy, Sustainability, holistic approach.